2011
DOI: 10.2139/ssrn.1632938
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences and Dynamics in Competition: The Role of Luck

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
55
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 63 publications
2
55
1
Order By: Relevance
“…This result is in line with Gill and Prowse (2010) who, using a series of competitions, find that the negative effect of losing in a competition on performance in a subsequent competition is stronger for women. While men react to losing by becoming more challenge seeking and women react by lowering their performance, both these reactions have similar negative effects on the likelihood of success and expected earnings.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…This result is in line with Gill and Prowse (2010) who, using a series of competitions, find that the negative effect of losing in a competition on performance in a subsequent competition is stronger for women. While men react to losing by becoming more challenge seeking and women react by lowering their performance, both these reactions have similar negative effects on the likelihood of success and expected earnings.…”
Section: Resultssupporting
confidence: 89%
“…Finally, Gill and Prowse (2010) also detect a gender difference whereby following a loss, women reduce their effort independent of the size of the prize whereas men only reduce their effort if the prize they failed to win was large enough.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…2009;Gill and Prowse, 2014;Almås et al, 2016) and that women shy away from competition much more often than men (seminal paper by Niederle and Vesterlund, 2007; see also Booth and Nolen, 2012;Datta Gupta et al, 2013;Brandts et al, 2014;Buser et al 2014;Sutter and Glätzle-Rützler, 2015;Flory et al, 2015;Saccardo et al 2017).2 Since firms often use tournament payment and promotion schemes (Eriksson, 1999;Bognanno, 2001), a lower inclination of women towards competition can help explain to some extent why they are less often promoted and end up with lower wages.3 Providing empirical evidence in this vein, McGee et al (2015) show on the basis of US data that women are less likely than men to be remunerated with a competitive compensation package and that this can explain part of the wage gap between the two genders.…”
Section: Introductionmentioning
confidence: 99%
“…A number of authors have investigated competition among employees, (e.g., Haan, Offerman & Sloof, 2015;Lazear, 1989;Van Ours & Ridder, 1995), and as a result, the motivational factors in such competitions have been revealed: for instance, winning prizes. In this regard, Gill and Prowse (2014) found that competition in a promoted tournament for winning a prize is a ubiquitous phenomenon in the labour market. Delfgaauw, Dur, Sol and Verbeke (2013), by observing 128 Dutch retail chain stores, deduced that conducting a sales competition among employees has a significant effect on sales growth, and that employees are not motivated only by the aim of gaining more rewards, but also, by winning the competition, as predicted by so-called tournament theory.…”
Section: Introductionmentioning
confidence: 99%